2019
DOI: 10.4149/bll_2019_104
|View full text |Cite
|
Sign up to set email alerts
|

Platelet mitochondrial bioenergetic analysis in patients with nephropathies and non-communicable diseases: a new method

Abstract: OBJECTIVES: To test the hypothesis if mitochondrial bioenergetic function analyzed in circulating platelets may represent peripheral signature of mitochondrial dysfunction in nephropathy associated to noncommunicable human diseases such as cardiovascular diseases, diabetes and with statins treatment. METHODS: High-resolution respirometry was used for analysis of mitochondrial bioenergetics in human platelets isolated from peripheral blood. This method is less-invasively compared to skeletal muscle biopsy. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Increased levels of total antioxidant capacity in diabetic hemodialyzed patients after CoQ 10 supplementation were documented (41). In agreement with others, we suppose that CoQ 10 supplementation could be important for improving the kidney function, and that clinical monitoring of platelet mitochondrial function, and plasma and platelet CoQ 10 levels could be important for determining the dosage of CoQ 10 supplementation (42,43,44,45,46,47).…”
Section: Plasma Coq 10-total In Subgroups Of Ckd Patients With Concomsupporting
confidence: 90%
“…Increased levels of total antioxidant capacity in diabetic hemodialyzed patients after CoQ 10 supplementation were documented (41). In agreement with others, we suppose that CoQ 10 supplementation could be important for improving the kidney function, and that clinical monitoring of platelet mitochondrial function, and plasma and platelet CoQ 10 levels could be important for determining the dosage of CoQ 10 supplementation (42,43,44,45,46,47).…”
Section: Plasma Coq 10-total In Subgroups Of Ckd Patients With Concomsupporting
confidence: 90%
“…Increased respiration in intact platelets in patients after fluvastatin and atorvastatin treatment, in patients with diabetes mellitus, and in dialyzed patients was found [39]. Opposite results-decreased respiration in intact platelets-were reported in depressive patients [18].…”
Section: Discussionmentioning
confidence: 93%
“…Basal mitochondrial oxygen consumption in permeabilized platelets with Complex I-linked substrates (step 1PM) in CKD-ALL patients was slightly decreased vs. the control group (Figure 2). A previous study showed damaged CI-linked respiration in a patient after renal transplantation and strongly impaired CI-linked respiration in a patient with thrombocytopenia [39]. Decreased Complex I-linked respiration in permeabilized platelets in humans after statins treatment has been reported, suggesting the use of the respirometric analysis of mitochondrial function in platelets for studying changes in cellular energy metabolism in patients treated with statins [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, metabolically highly active but homogenous PLTs might be a valuable surrogate to investigate systemic changes of mitochondrial function, since they are involved in a variety of systemic reactions (e.g., hemostasis, immunoregulation, inflammation or oxidative stress) [18][19][20]. Assessing PLT bioenergetics as a systemic marker has been performed in the context of various diseases [15,19,[21][22][23][24][25][26][27][28] as well as training studies [29][30][31][32][33]. However, changes in PLT bioenergetics after an ultramarathon competition in the context of a field study has not been assessed so far.…”
Section: Introductionmentioning
confidence: 99%